PENDAMPINGAN DALAM PENGEMBANGAN KURIKULUM PADA MUATAN LOKAL (PENGUASAAN KITAB KUNING) DI MTS. SALAFIYAH SYAFI’IYAH PUTRA SUKOREJO SITUBONDO - Muhamad Abdul Manan; Mahmudi Bajuri (LP2M Universitas Ibrahimy, 2019)
Permendiknas No. 22 of 2006 concerning Content Standards states that the School-Based Curriculum (KTSP) containing several main subjects and local contents (mulok) which must be given in all education levels. Guidance in reading the yellow book (BMK) is one part of curriculum development on local content in MTs Salafiyah Syafi’iyah Putra who emphasizes the mastery in reading the yellow book. Assistance is carried out in learning activities, which include various methods, such as khataman, discussion, and lecture as an effort to master the yellow book, as material for students to face the madrasah competency test, which we need to know that there are two competency that must be mastered by MTs Salafiyah Syafi’iyah Putra students as one of the requirements for graduation.